Sistem Informasi Penjualan Online Berbasis Web Dengan Metode Prototype (Studi Kasus: Elladine Official) - Hendro Tirta Anggardi; Afiudin Bayu Seto; Fauzan Al Ihsan (CV. Shofanah Media Berkah, 2023)
Internet technology has been proven to be an effective and efficient information medium in disseminating information that can be accessed by anyone, anytime and anywhere. Internet technology has a very large effect on commerce or business. Only from home or office space, prospective buyers can view products on a computer screen, access information, order, and pay with the available options. Prospective buyers can save time and costs because they don't have to come to the store or place of transaction so they can make decisions quickly from where they are seated. Online transactions can connect sellers and prospective buyers directly without being limited by space and time. That means online sales transactions have potential buyers from all over the world. In addition, the development of the company feels considered rather slow. Therefore an online sales system is designed using web or internet media to minimize sales processing time to increase sales volume so that company revenue can increase. In this study, the authors used the waterfall method and observation. The implementation shows login and registration processes, inputting: product data, product orders, sales, payments, complaints, and testimonials. It can be concluded that this system gets information and reports easily. This system also makes it easier for consumers to purchase the desired product. Controls in data recording and security can be handled properly because each user has their password and is given a menu according to the process to be executed. Website visitors who do not register as consumers, can still see the products being sold and also testimonials that have been made by consumers.